2021
DOI: 10.7498/aps.70.20210564
|View full text |Cite
|
Sign up to set email alerts
|

Quenched solitons and shock waves in Bose-Einstein condensates

Abstract: The Bose-Einstein condensate (BEC) formed by ultracold atomic gases provides an ideal platform for studying various quantum phenomena. In this platform, researchers have explored in depth the important equilibrium and steady phenomena including superfluidity, vortices, and solitons, and recently started to study nonequilibrium problems. In a classical system, nonequilibrium problems, such as explosion, usually occur together with shock waves, which is presented when the explosion speed is larger than the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…While for a 1D BEC in a box trap under the same quench, n−1 grey solitons at each edge can be excited and further move away from the edges, if η ≡ n is an integer. [20] In both situations, if η is not an integer, there will be extra excitations [20][21][22] while the number of excited solitons is the same as that of taking the ceiling of η, i.e., n = η . For a 2D BEC, we find that the condition of the number of excited RDSs is different from that in a 1D BEC.…”
Section: Solitons Excited In a Disk Trapmentioning
confidence: 99%
See 1 more Smart Citation
“…While for a 1D BEC in a box trap under the same quench, n−1 grey solitons at each edge can be excited and further move away from the edges, if η ≡ n is an integer. [20] In both situations, if η is not an integer, there will be extra excitations [20][21][22] while the number of excited solitons is the same as that of taking the ceiling of η, i.e., n = η . For a 2D BEC, we find that the condition of the number of excited RDSs is different from that in a 1D BEC.…”
Section: Solitons Excited In a Disk Trapmentioning
confidence: 99%
“…The outcome of the interaction quench may be either solitons or Bogoliubov modes, and even shock waves. [21] Specifically, by setting the ratio of the after-and before-quench interaction strength as η 2 , Halperin et al found that, if η is an integer, an initial half black soliton localized at an edge of a box trap will decay into η − 1 moving grey solitons without other excitation. Such a method possesses a solid foundation elaborated by the inverse scattering theory.…”
Section: Introductionmentioning
confidence: 99%
“…8c®3 lfN [32] !1AE [33] !YÅ [34] !p íN [35] ! BEC [36] õ ‡Ôn+•uyÀÂÅ, ¿òÙA^ š [37,38] !ó § [39−42] ! )Ô‰AE +•.…”
mentioning
confidence: 99%